Peran Pendidikan dalam Membangun Sikap Ketuhanan yang Maha Esa - Al Firman; Yakobus Ndona (Jurnal Bintang Pendidikan Indonesia, 2024)
Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble morals and skills needed by themselves and society. The aim of this research is to find out how education plays a role in cultivating and building an attitude of belief in the Almighty God. In this research, the Library Research method (library research) is used, studying literature and other scientific works related to the problem being researched in order to obtain a theoretical basis. as well as laws related to the discussion or problem being studied. The results of the discussion from this research are that education has a very important role in building an attitude of belief in Almighty God. Through teaching religious values, students gain a deep understanding of divine teachings and principles, which become the basis for their character development.